Business Education and the Entreprenuership Education Agenda: A Synergy for Unemployment Reduction in Nigeria - Chinasa, Obi Emmanuel (Richtmann Publishing, 2012)
Unemployment or the search for paid employment in Nigeria has become endemic. This is support by theclaims that Nigerian education system is bookish and academic oriented and lacked vocational andentrepreneurial values. Hence, the need to refocus education towards programmes that will inculcateknowledge and skills that prepare citizens for employment and self-reliance, economic diversification andsustainable development. The paper examines the business education programme and theentrepreneurship Education Agenda as a Synergy for the reduction of unemployment in Nigeria. The paperconcludes that unemployment in Nigeria requires a combination therapy as the synergy will bring about anew pedagogy in which students are prepared with knowledge and practical skills but more especiallycreativity, spirit of initiative, responsibility, capacity for confronting risk and the boldness to start smallscale business on graduation. This will reduce unemployment or the thinking for paid employment.